Public perception of Jan Aushadhi medicines in Mysore city: a prospective observational study - M. D., Mahima Prakash; Panyala, Sai Meenakshitha; James, Jennifer; Krishna, Mahima H.; Jaidev Kumar, B. R. (International Journal Of Community Medicine And Public Health, 2025)
Background: Generic medicines are crucial to ensuring affordable healthcare. The Jan Aushadhi scheme (JAS) was initiated in India to provide quality drugs at lower costs. However, public perception of such medicines remains understudied in certain regions. Methods: A prospective observational study was conducted among the general population over six months. Data from all participants were collected using a validated bilingual questionnaire distributed through social media platforms, and the responses were compiled in a Google Excel sheet. Descriptive statistical methods were used for data analysis. Results: Among the 1,316 participants, 54.86% were female, and a majority (55.24%) were aged between 18 and 25 years. Awareness of the JAS was reported by 68% of respondents, while 66% were able to distinguish between branded and generic medicines. Overall, 75% expressed a preference for generic medicines over branded ones; however, the remaining participants opted for branded medications. 27% believed that generic medicines were more effective than branded, whereas 86% agreed that Jan Aushadhi medicines were more cost-effective. Conclusions: Despite high perceived affordability, knowledge gaps about the quality and effectiveness of Jan Aushadhi medicines remain. Awareness campaigns and policy efforts are needed to promote trust and utilization.